1977
DOI: 10.1128/aac.12.2.157
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Pharmacology of Cefaclor and Cephalexin

Abstract: Two cephalosporin antibiotics, cefaclor and cephalexin, were administered orally to healthy, adult male volunteers for comparison of their pharmacological properties. In doses of 250 mg orally, cefaclor produced a peak serum concentration of 6.01 + 0.55 (standard deviation [SD]) ,ug/ml compared with 9.43 + 2.36 ,g/ml for cephalexin (P < 0.01). The half-lives were 0.58 + 0.07 (SD) h and 0.80 + 0.12 (SD) h, and elimination constants were 1.22 + 0.15 and 0.88 + 0.13 h-1 for cefaclor and cephalexin, respectively (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
1

Year Published

1978
1978
1993
1993

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(22 citation statements)
references
References 5 publications
2
19
1
Order By: Relevance
“…This means that, at a CorCcr of 100 ml/min, 29% of cefaclor was probably being excreted by a nonrenal route, compared with only 6% for cephalexin. This is in close agreement with the 62% urinary recovery in this study and our previous study in which we found 70% urinary recovery for cefaclor and 96% recovery for cephalexin (7). In any event, the half-life of cefaclor of 2 to 3 h for a CorCcr of 0 suggests that drug accumulation will be negligible even for a 6-h dosage regimen in anephric patients.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This means that, at a CorCcr of 100 ml/min, 29% of cefaclor was probably being excreted by a nonrenal route, compared with only 6% for cephalexin. This is in close agreement with the 62% urinary recovery in this study and our previous study in which we found 70% urinary recovery for cefaclor and 96% recovery for cephalexin (7). In any event, the half-life of cefaclor of 2 to 3 h for a CorCcr of 0 suggests that drug accumulation will be negligible even for a 6-h dosage regimen in anephric patients.…”
Section: Discussionsupporting
confidence: 92%
“…The metabolism of cefaclor has been examined in three species of laboratory animals (13) and in normal volunteers (7). Cefaclor is chemically similar to other cephalosporins recently reviewed by Nightingale et al (8).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although its in vitro activity against Escherichia coli, Klebsiella pneumoniae, and Proteus mirabilis is similar in range to those of other oral cephalosporins, cefaclor has been shown to be signiflcantly more active at lower and more easily attainable concentrations against the cephalosporin-susceptible Enterobacteriaceae as well as staphylococci, streptococci, and gonococci (2, 9-11). The antibiotic is excreted in high concentrations in the urine of humans and experimental animals (7,12).…”
mentioning
confidence: 99%